2016
DOI: 10.3892/ol.2016.4608
|View full text |Cite
|
Sign up to set email alerts
|

Integration and bioinformatics analysis of DNA-methylated genes associated with drug resistance in ovarian cancer

Abstract: Abstract.The main obstacle to the successful treatment of ovarian cancer is the development of drug resistance to combined chemotherapy. Among all the factors associated with drug resistance, DNA methylation apparently plays a critical role. In this study, we performed an integrative analysis of the 26 DNA-methylated genes associated with drug resistance in ovarian cancer, and the genes were further evaluated by comprehensive bioinformatics analysis including gene/protein interaction, biological process enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…Ovarian cancer is the most deadly gynecological malignancy, with more than 120 000 new deaths in the world every year, which pose a serious threat to women’s health [ 1 3 ]. Approximately 70% of patients with ovarian cancer are diagnosed in the later period, and the 5-year survival rate for ovarian cancer is only 30–40% [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer is the most deadly gynecological malignancy, with more than 120 000 new deaths in the world every year, which pose a serious threat to women’s health [ 1 3 ]. Approximately 70% of patients with ovarian cancer are diagnosed in the later period, and the 5-year survival rate for ovarian cancer is only 30–40% [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Multidrug resistance (MDR) is the main cause of chemotherapy failure in ovarian cancer. [ 2 ] Therefore, ovarian cancer has a poor prognosis, with only 40% of patients surviving for 5 years. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicated that loss of expression due to hypermethylation of hMSH2 upstream region might induce platinum resistance in EOC patients. In the earlier literature hypermethylation of another essential MMR gene, hMLH1 was observed in cisplatin-resistant EOC patients [25, 26]. While whether loss of hMSH2 expression caused by hypermethylation of hMSH2 promoter contributed to platinum resistance or not in EOC was unclear previously.…”
Section: Discussionmentioning
confidence: 99%